Dysregulation of the MEK/ERK/MNK1 signalling cascade by middle T antigen of the trichoydsplasia spinulosa polyomavirus. (6th June 2017) - Wu, J.H.; Narayanan, D.; Simonette, R.A.; Rady, P.L.; Tyring, S.K.
Abstract: Background: Trichodysplasia spinulosa (TS) is a disfiguring folliculocentric cutaneous disease caused by infection with the trichodysplasia spinulosa polyomavirus (TSPyV). The TSPyV genome contains splice variants encoding the middle tumour (mT) antigen, although the potential role for TSPyV mT antigen in disease development remains unknown. Objective: The current study was designed to investigate the mechanistic properties of TSPyV mT antigen, which may further our understanding of TS pathogenesis and provide insight into potential therapies. Methods: A lentiviral packaging system was used to create an inducible cell line expressing TSPyV mT antigen. Proteins were extracted, separated by SDS‐PAGE and subjected to Western blot analysis. Co‐immunoprecipitation experiments and mutational analyses were also performed to evaluate protein–protein interactions of mT antigen. Results: We describe a novel mechanism of action for mT antigen that involves hyperactivation of MEK, ERK and MNK1. Our findings suggest that dysregulation of these key signalling molecules depends upon TSPyV mT antigen interaction with protein phosphatase 2A (PP2A) via intact Zn binding motifs. Conclusion: Given that PP2A interaction and MEK/ERK/MNK1 phosphorylation are associated with high levels of cell proliferation and inflammation, our findings provide new evidence that TSPyV mT antigen may contribute to the pro‐proliferative conditions that lead to TS development.